Overrepresentation of T allele of MCT1 rs1049434 polymorphism in the group of Polish elite sportsmen - Cieszczyk, P.; Huminska-Lisowska, K.; Dzitkowska-Zabielska, M.; Leonska-Duniec, A.; Bojarczuk, A. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Both the scientific and sporting communities agree that genetic factors contribute to athletic performance. The estimated percentage of the heredity of athletic status is 66%. Currently, around 155 genetic markers are linked to endurance and strength/power traits. Thus, we aimed to investigate whether selected MCT1 rs1049434, NRF-2 rs12594956, MYBPC3 rs1052373, HFE rs1799945 polymorphisms, which have been described as associated with elite sprint/power abilities, are associated with endurance capacity of the high-elite Polish athletes.